Nonrapid eye movement sleep electroencephalographic oscillations in idiopathic rapid eye movement sleep behavior disorder: a study of sleep spindles and slow oscillations. Issue 2 (22nd August 2020) - Sunwoo, Jun-Sang; Cha, Kwang Su; Byun, Jung-Ick; Jun, Jin-Sun; Kim, Tae-Joon; Shin, Jung-Won; Lee, Soon-Tae; Jung, Keun-Hwa; Park, Kyung-Il; Chu, Kon; Kim, Manho; Lee, Sang Kun; et al.
Abstract: Study Objectives: We investigated electroencephalographic (EEG) slow oscillations (SOs), sleep spindles (SSs), and their temporal coordination during nonrapid eye movement (NREM) sleep in patients with idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD). Methods: We analyzed 16 patients with video-polysomnography-confirmed iRBD (age, 65.4 ± 6.6 years; male, 87.5%) and 10 controls (age, 62.3 ± 7.5 years; male, 70%). SSs and SOs were automatically detected during stage N2 and N3. We analyzed their characteristics, including density, frequency, duration, and amplitude. We additionally identified SO-locked spindles and examined their phase distribution and phase locking with the corresponding SO. For inter-group comparisons, we used the independent samples t -test or Wilcoxon rank-sum test, as appropriate. Results: The SOs of iRBD patients had significantly lower amplitude, longer duration ( p = 0.005 for both), and shallower slope ( p < 0.001) than those of controls. The SS power of iRBD patients was significantly lower than that of controls ( p = 0.002), although spindle density did not differ significantly. Furthermore, SO-locked spindles of iRBD patients prematurely occurred during the down-to-up-state transition of SOs, whereas those of controls occurred at the up-state peak of SOs ( p = 0.009). The phase of SO-locked spindles showed a positive correlation with delayed recall subscores ( p = 0.005) but not with tonic or phasic electromyography activity during REM sleep. Conclusions: In this study, we found abnormal EEG oscillations during NREM sleep in patients with iRBD. The impaired temporal coupling between SOs and SSs may reflect early neurodegenerative changes in iRBD.